Magic tricks from the tree house : a fun companion to Magic Tree House #50 : hurry up, Houdini! - Osborne, Mary Pope; Boyce, Natalie Pope (Osborne, Mary Pope. Magic tree house series., 2013)
A chapter-book companion to the fiftieth Magic Tree House adventure outlines how to perform basic magic tricks and is complemented by facts about famous historical magicians.